1990
DOI: 10.1128/jvi.64.3.1079-1085.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface expression of human cytomegalovirus (HCMV) gp55-116 (gB): use of HCMV-recombinant vaccinia virus-infected cells in analysis of the human neutralizing antibody response

Abstract: Cell surface expression of the human cytomegalovirus (HCMV) major envelope glycoprotein complex, gp55-116 (gB), was studied by using monoclonal antibodies and an HCMV gp55-116 (gB) recombinant vaccinia virus. HCMV-infected human fibroblasts and recombinant vaccinia virus-infected HeLa cells expressed three electrophoretically distinct proteins of Mr 170,000, 116,000, and 55,000 on their surface. These species have been previously identified within infected cells and purified virions. Two unique neutralizing ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(124 citation statements)
references
References 39 publications
2
121
0
Order By: Relevance
“…The selection of gB and gM proteins as antigens was based on previous studies showing them as the main targets for neutralizing antibodies. 29,32,33 Due to the small amount of mouse sera, we did not perform a microneutralization assay and instead, used the levels of binding antibodies to reflect the effectiveness of primeboost immunizations. For gB antibody responses, recombinant gB ( Fig.…”
Section: Construction and Evaluation Of Dna Vaccines Expressing Hcmv mentioning
confidence: 99%
“…The selection of gB and gM proteins as antigens was based on previous studies showing them as the main targets for neutralizing antibodies. 29,32,33 Due to the small amount of mouse sera, we did not perform a microneutralization assay and instead, used the levels of binding antibodies to reflect the effectiveness of primeboost immunizations. For gB antibody responses, recombinant gB ( Fig.…”
Section: Construction and Evaluation Of Dna Vaccines Expressing Hcmv mentioning
confidence: 99%
“…If a prototypic IgG-Fc domain fulfilling the requirements of selective interaction is found, this module could be fused to a large number of HCMV-reactive IgG-Fab domains. Such a cocktail of monoclonal recombinant Abs will be necessary to deal with the interstrain diversity of the major HCMV neutralising epitopes present on the glycoproteins gB and gH [119][120][121] in order to generate widely effective protection. The MCMV animal model could serve as an optimal test tube to generate experimental evidence in vivo for an IgG-Fc-dependent subversive role of vFcgRs in viral pathogenesis in a natural host.…”
Section: Perspective: Engineering Virus-specific Iggs Resisting Vfc;rs?mentioning
confidence: 99%
“…Secondly, the C23reactive epitope may be less immunogenic in some individuals. A large proportion (40-70%) of the neutralizing antibody response to natural HCMV infection appears to be directed against gB [Britt et al, 1990;Marshall et al, 19921, but Kniess et al [1991] reported that most neutralizing antibodies are directed against the gB epitope AD-1, which is located around amino acid 616 in gB116. However, we did not test reactivity with AD-1 and comparative studies are needed.…”
Section: C138mentioning
confidence: 99%